Interannual adjustments in stomatal and leaf morphological traits of European beech (Fagus sylvatica L.) demonstrate its climate change acclimation potential - Petrik, P; Petek-Petrik, A; Kurjak, D; Mukarram, M; Klein, T; Gömöry, D; Střelcová, K; Frýdl, J; Konôpková, A (Plant biology (Stuttgart, Germany), 2022)
The current projections of climate change might exceed the ability of European forest trees to adapt to upcoming environmental conditions. However, stomatal and leaf morphological traits could greatly influence the acclimation potential of forest tree species subjected to global warming, including the single most important forestry species in Europe, European beech. We analysed stomatal (guard cell length, stomatal density and potential conductance index) and leaf (leaf area, leaf dry weight and leaf mass per area) morphological traits of ten provenances from two provenance trials with contrasting climates between 2016 and 2020. The impact of meteorological conditions of the current and preceding year on stomatal and leaf traits was tested by linear and quadratic regressions. Ecodistance was used to capture the impact of adaptation after the transfer of provenances to new environments. Interactions of trial-provenance and trial-year factors were significant for all measured traits. Guard cell length was lowest and stomatal density was highest across beech provenances in the driest year, 2018. Adaptation was also reflected in a significant relationship between aridity ecodistance and measured traits. Moreover, the meteorological conditions of the preceding year affected the interannual variability of stomatal and leaf traits more than the meteorological conditions of the spring of the current year, suggesting the existence of plant stress memory. High intraspecific variability of stomatal and leaf traits controlled by the interaction of adaptation, acclimation and plant memory suggests a high acclimation potential of European beech provenances under future conditions of global climate change.
Keywords: stomatal size; buk (rod); Plant Leaves; ecodistance; Climate Change; plant memory; Fagus; stromy; Trees; Acclimatization; Adaptation; listy rostlin; klimatické změny; leaf morphology; provenance; stomatal density; aklimatizace